Relating the South African soil taxonomy to the World Reference Base for soil resources - van Huyssteen, Cornie (UJ Press, 2020)
The South African Taxonomic soil classification system (SAT) is well established and utilised in South Africa. However, it is not internationally well known and therefore the need arose to provide a tool by which South African soil taxonomists can convert South African soil classifications and profile descriptions to the international classifications of the World Reference Base (WRB) for soil resources. The diagnostics and tacit knowledge presented in this publication are therefore based on the SAT and the WRB. When necessary, further substantiation was derived from the Land Type Survey of South Africa. The adopted procedure is effective in providing a reasonable classification based on the South African soil forms and families, while excluding certain WRB soil groups and qualifiers, because these are irrelevant to South African taxonomy. Lastly, this publication also highlights some peculiarities, omissions and inconsistencies observed between the SAT and WRB.